The Influence of User Experience (UX) on Digital Information Services in Libraries Universitas Negeri Padang - Waliatun Masabih Sayalin; Desriyeni (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study was motivated by the rapid development of information technology, which has encouraged libraries to provide digital information services that are fast, easily accessible, and capable of meeting users' information needs. The success of digital information services is determined not only by the availability of technology and the completeness of information but also by users' experiences (User Experience [UX]) when interacting with the system. Therefore, this study aims to examine the effect of User Experience (UX) on digital information services at the Library of Universitas Negeri Padang. This study employed a quantitative method using descriptive and verification approaches. The study population consisted of all users of the digital information services at the Library of Universitas Negeri Padang, totaling 5,824 users. The sample was determined using the Slovin formula with a 10% margin of error, resulting in 98 respondents. Data were collected through a questionnaire using a five-point Likert scale. The data were analyzed using descriptive statistics and simple linear regression with the assistance of SPSS software. The User Experience (UX) variable was measured using five indicators: ease of use, ease of access, interface clarity, information quality, and user comfort. Meanwhile, digital information services were measured through service reliability, access speed, information accuracy and completeness, ease of obtaining information, and user satisfaction. The findings indicate that User Experience (UX) has a positive and significant effect on digital information services at the Library of Universitas Negeri Padang. The better the users' experience, the higher the perceived quality of digital information services. These findings suggest that ease of use, accessibility, interface clarity, information quality, and user comfort should become primary considerations in the development of library digital information services. This study is expected to serve as an evaluation reference for library managers in improving digital-based services that are more effective, efficient, and user-oriented.